What comes first?: the dynamics of cerebral oxygenation and blood flow in response to changes in arterial pressure and intracranial pressure after head injury - Budohoski, Karol P.; Diedler, Jennifer (British journal of anaesthesia, 2012)
Background Brain tissue partial oxygen pressure (PbtO2) and near-infrared spectroscopy (NIRS) are novel methods to evaluate cerebral oxygenation. We studied the response patterns of PbtO2, NIRS, and cerebral blood flow velocity (CBFV) to changes in arterial pressure (AP) and intracranial pressure (ICP). Methods Digital recordings of multimodal brain monitoring from 42 head-injured patients were retrospectively analysed. Response latencies and patterns of PbtO2, NIRS-derived parameters [tissue oxygenation index (TOI) and total haemoglobin index (THI)], and CBFV reactions to fluctuations of AP and ICP were studied. Results One hundred and twenty-one events were identified. In reaction to alterations of AP, ICP reacted first [4.3 s; inter-quartile range (IQR) −4.9 to 22.0 s, followed by NIRS-derived parameters and CBFV (10.9 s; IQR: −5.9 to 39.6 s, 12.1 s; IQR: −3.0 to 49.1 s, 14.7 s; IQR: −8.8 to 52.3 s for THI, CBFV, and TOI, respectively), with PbtO2 reacting last (39.6 s; IQR: 16.4 to 66.0 s). The differences in reaction time between NIRS parameters and PbtO2 were significant (P<0.001). Similarly when reactions to ICP changes were analysed, NIRS parameters preceded PbtO2 (7.1 s; IQR: −8.8 to 195.0 s, 18.1 s; IQR: −20.6 to 80.7 s, 22.9 s; IQR: 11.0 to 53.0 s for THI, TOI, and PbtO2, respectively). Two main patterns of responses to AP changes were identified. With preserved cerebrovascular reactivity, TOI and PbtO2 followed the direction of AP. With impaired cerebrovascular reactivity, TOI and PbtO2 decreased while AP and ICP increased. In 77% of events, the direction of TOI changes was concordant with PbtO2. Conclusions NIRS and transcranial Doppler signals reacted first to AP and ICP changes. The reaction of PbtO2 is delayed. The results imply that the analysed modalities monitor different stages of cerebral oxygenation.